Anorexia Athletica and Relative Energy Deficiency - Schöffl, Isabelle; Schöffl, Volker (Springer International Publishing, 2022)
Climbing belongs to the sport disciplines in which low body weight represents an advantage. Many athletes therefore use at least one unhealthy way of controlling their weight. The consequence is relative energy deficiency in sport or RED-S with possible long-term complications like dental caries, osteoporosis, renal insufficiency, anemia, and recognized psychiatric disorders. The most common psychiatric disorders resulting from RED-S, formerly titled anorexia athletica, are true anorexia nervosa and depression. Some of the athletes are so convinced of the dependence of their weight on their performance, and this wrong belief is so firmly ingrained that they suffer their whole life from the mental consequences. Early detection of possible warning signs and providing assistance early on is therefore a priority in order to reduce long-term damage.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Anorexia athletica; Athlete female triad; RED-S

Athlete's Heart in Elite Sport Climbers: Cardiac Adaptations Determined Using ECG and Echocardiography Data - Schöffl, Isabelle; Wüstenfeld, Jan; Jones, Gareth; Dittrich, Sven; Lutter, Chris; Schöffl, Volker (Wilderness & Environmental Medicine, 2020)
Introduction: Sudden cardiac death in a young athlete is the leading cause of mortality in athletes during sport. Specific knowledge about cardiac adaptations are necessary for a better understanding of the underlying causes of such events. Methods: A retrospective analysis of the electrocardiogram and echocardiographic data obtained during the yearly medical examination of the entire German junior national climbing team was undertaken. First, data from 1 examination were used. In a second step, data from 2 examinations spaced 2 y apart were analyzed for a selected subgroup to gain more knowledge about adaptations to climbing. The data from the subgroup were compared to an age- and sex-matched control group of Nordic skiers from the German junior national Nordic skiing team. Results: Forty-seven young climbers (20 girls, 27 boys) were examined once. There were no pathological findings in the electrocardiogram or echocardiography. The left ventricular (LV) measurements fell between those for athletes and nonathletes. Eight boys and 6 girls from this group were tested twice over a timeframe of 27.5 mo. All LV measurements increased over time. After 2 y, the measurements from the climbers were comparable to those of the Nordic skiers. Conclusions: Hypertrophic cardiomyopathy (hypertrophy of the LV) is the leading cause of sudden cardiac death in athletes. An increase in LV dimensions was observed in the young climbers in this study. LV dimensions being comparable to high-level Nordic skiers after 2 y in the national team imply structural changes over time in this cohort.
CRIS-Team Scopus Importer:2020-11-20
Keywords: adolescent athlete; cardiomyopathy; concentric hypertrophy; eccentric hypertrophy; pediatric cardiology; sports ability test

Cardiopulmonary function in paediatric post-COVID-19: a controlled clinical trial - Schöffl, Isabelle; Raming, Roman; Tratzky, Jan Philipp; Regensburger, Adrian; Kraus, Calvin; Wällisch, Wolfgang; Trollmann, Regina; Wölfle, Joachim; Dittrich, Sven; Heiß, Rafael; Knieling, Ferdinand; Weigelt, Annika (European Journal of Pediatrics, 2024)
Recently, the importance of post-COVID-19 in children has been recognized in surveys and retrospective chart analysis. However, objective data in the form of cardiopulmonary exercise test as performed in adults suffering from this condition are still lacking. This study aimed to investigate the cardiopulmonary effects of post-COVID-19 on children and adolescents. In this cross-sectional study (the FASCINATE study), children fulfilling the criteria of post-COVID-19 and an age- and sex-matched control group underwent cardiopulmonary exercise testing on a treadmill and completed a questionnaire with regard to physical activity before, during and after the infection with SARS-CoV-2. We were able to recruit 20 children suffering from post-COVID-19 (mean age 12.8 ± 2.4 years, 60% females) and 28 control children (mean age 11.7 ± 3.5 years, 50% females). All participants completed a maximal treadmill test with a significantly lower V ˙ O 2peak in the post-COVID-19 group (37.4 ± 8.8 ml/kg/min vs. 43.0 ± 6.7 ml/kg/min. p = 0.019). This significance did not persist when comparing the achieved percentage of predicted V ˙ O 2peak . There were no significant differences for oxygen pulse, heart rate, minute ventilation or breathing frequency. Conclusion: This is the first study to investigate post-COVID-19 in children using the cardiopulmonary exercise test. Although there was a significantly reduced V ˙ O 2peak in the post-COVID-19 group, this was not true for the percent of predicted values. No pathological findings with respect to cardiac or pulmonary functions could be discerned. Deconditioning was the most plausible cause for the experienced symptoms. Trial registration: clinicaltrials.gov, NCT054445531, Low-field Magnetic Resonance Imaging in Pediatric Post Covid-19—Full Text View—ClinicalTrials.gov. What is Known: • The persistence of symptoms after an infection with SARS-CoV 2, so-called post-COVID-19 exists also in children. • So far little research has been conducted to analyze this entity in the pediatric population. What is New: • This is the first study proving a significantly lower cardiopulmonary function in pediatric patients suffering from post-COVID-19 symptoms. • The cardiac and pulmonary function appear similar between children suffering from post-COVID-19 and those who don’t, but the peripheral muscles seem affected.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Cardiopulmonary exercise testing; Exercise capacity; Fitness; Physical activity; Post-COVID; VO

Climbing Medicine: A Practical Guide - Schöffl, Volker; Schöffl, Isabelle; Lutter, Christoph; Hochholzer, Thomas (Springer International Publishing, 2022)
This book comprehensively discusses the medical aspects of sports climbing, a still young but emerging sport, which will be one of the disciplines at the Tokyo Olympics. Its rapid development from niche to popular sport has been accompanied by an increase in the number of climbing-sports-specific injuries and has attracted growing interest within the sports medicine community. Gathering expertise from around the globe, the book covers all aspects related to this discipline – from physiology, biomechanics and anatomy through upper and lower extremity injuries to cardiology, gynecology, pediatric and adolescent conditions. Following a coherent structure, each chapter equips readers with evidence-based diagnostic and therapeutic guidelines. Enriched by a wealth of pictures, this manual offers a timely and up-to-date resource for sports physicians, orthopedic surgeons and traumatologists, as well as trainers, physiotherapists and other health professionals involved in climbing.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Hand injuries; Mountain sports; Physiology of climbing; Rock climbing; Sports climbing

COPHYD (Corona Owed Physical Deficiency): The Impact of Lockdown on Cardiopulmonary Function in Paediatric Cardiology Patients - Stabler, Tim; Weigelt, Annika; Rottermann, Kathrin; Wällisch, Wolfgang; Hübner, Matthias; Dittrich, Sven; Schöffl, Isabelle (Klinische Pädiatrie, 2022)
Introduction Due to the Corona-lockdowns the closure of sports facilities and schools has led to a decline in physical activity (PA) for months. PA is essential for maintaining cardiopulmonary function assessed by peak oxygen uptake. Since peak oxygen uptake represents the best predictor for mortality and morbidity in children with congenital heart disease the impact of lockdowns on this parameter is vital. Methods We evaluated retrospectively cardiopulmonary exercise data from our patient collective from before lockdown with twin-paired data from during lockdown. The twin-pairing was achieved by matching patients with similar heart disease, age, sex, and test method. Cardiopulmonary exercise testing was achieved on either the treadmill or the bicycle. Results We were able to twin-pair 90 cases (26 twins with heart disease and 19 healthy twins). There was a significant decrease of cardiopulmonary function (V?O (2) peak: 35.7 +/- 9.8 vs.30.4 +/- 10.6) in the heart disease cohort along with a significant decrease in peak oxygen pulse (13.3 +/- 4.1 vs. 11.4 +/- 4.5), and peak minute ventilation (V ?E: 83.05 +/- 29.08 vs.71,49 +/- 24.96). The healthy children improved over the timeframe, but this only reached significance for peak minute ventilation (81.72 +/- 25.79 vs.97.94 +/- 31.4). Conclusion We observed a significant decline of peak oxygen uptake during lockdown in the group of congenital heart disease (CHD) patients. This involved a loss of cardiac function as well as pulmonary function. This could be explained by limited access to sports facilities and restriction of regular daily movement due to school closure and overprotection. Healthy children improved their pulmonary function. This might be an indication of an improvement of exercise during confinement.
CRIS-Team WoS Importer:2022-10-14

Fitter Fontans for future—Impact of physical exercise on cardiopulmonary function in Fontan patients - Weigelt, Annika; Fritsch, Regina; Rottermann, Kathrin; Wällisch, Wolfgang; Moosmann, Julia; Dittrich, Sven; Purbojo, Ariawan; Schöffl, Isabelle (Frontiers in Cardiovascular Medicine, 2022)
Background: In Fontans, exercise tolerance is poorer compared to their healthy peers. Higher (Formula presented.) represents a strong predictor for mortality and morbidity in these patients. Cardiac rehabilitation programs have been shown to improve cardiopulmonary function in Fontans. More habitual physical activity should therefore lead to a better exercise tolerance. Methods: We performed cardiopulmonary exercise testing in 24 Fontan patients who had engaged in physical activity for a minimum of 3 h per week over their lifetime. As a control we performed cardiopulmonary exercise testing in 20 Fontan patients who had undertaken no physical activity or <3 h per week in the past. Results: A total of 44 Fontan patients was included (mean age 18.1 years). The mean parameters measured at peak exercise differed significantly between the active and inactive group (peak oxygen uptake [(Formula presented.)] of 34.0 vs. 25.0 ml/min/kg, peak heart rate (HR) of 169.8/min vs. 139.8/min). Even though the O2pulse and the EF did not differ significantly between both groups, N-Terminal-Pro-B-Type Natriuretic Peptide (NT-pro BNP) was significantly higher in the inactive group. The two groups did not differ with respect to their cardiac function determined by magnetic resonance imaging (MRI). (Formula presented.) was positively correlated with hours of sports performed by Fontans. Conclusions: (Formula presented.) and maximum HR were significantly higher in Fontans who had been physically active compared to those who had been inactive. The values reported in this study were higher than in other studies and reached normal values for (Formula presented.) for most Fontans in the physically active group. The positive correlation between (Formula presented.) and physical activity is an indicator of the importance of incorporating physical exercise programs into the treatment of Fontan patients.
CRIS-Team Scopus Importer:2022-10-07
Keywords: cardiopulmonary exercise testing (CPET); congenital heart disease; habitual exercise; peak oxygen uptake; sports and exercise medicine; TCPC; V̇O

Impact of premature birth on cardiopulmonary function in later life - Weigelt, Annika; Bleck, Steffen; Hübner, Matthias; Rottermann, Kathrin; Wällisch, Wolfgang; Morhart, Patrick; Abu-Tair, Tariq; Dittrich, Sven; Schöffl, Isabelle (European Journal of Pediatrics, 2023)
Pulmonary function is reduced in children after preterm birth. The variety of subgroups ranges from early to late preterm births. Limitations in pulmonary function can be observed even after late preterm birth without signs of bronchopulmonary dysplasia and/or history of mechanical ventilation. Whether this reduction in lung function is reflected in the cardiopulmonary capacity of these children is unclear. This study aims to investigate the impact of moderate to late premature birth on cardiopulmonary function. Cardiopulmonary exercise testing on a treadmill was performed by 33 former preterm infants between 8 and 10 years of age who were born between 32 + 0 and 36 + 6 weeks of gestation and compared with a control group of 19 children born in term of comparable age and sex. The former preterm children achieved comparable results to the term-born controls with respect to most of the cardiopulmonary exercise parameters (V˙O2peak43.9±6.6mlkgminminvs.41.9±8.8mlkg/min) . The only differences were in a slightly higher oxygen uptake efficiency slope (OUESof1.6±0.4vs1.4±0.4) and higher peak minute ventilation V˙Epeakof55.2±11.3ml/minvs.49.1ml±8.8/min) in the group of children born preterm. With respect to heart rate recovery (-35.3±13.8bpmvs.-37.2bpm±14.0after1min) and breathing efficiency (V˙E/V˙CO2of35.9±4.1vs34.0±4.6) , there were no significant differences. Conclusion: Children born preterm did not show limitations in cardiopulmonary function in comparison with matched controls. What is Known: • Preterm birth is associated with reduced pulmonary function in later life, this is also true for former late preterms. • As a consequence of being born premature, the lungs have not finished their important embryological development. Cardiopulmonary fitness is an important parameter for overall mortality and morbidity in children and adults and a good pulmonary function is therefore paramount. What is New: • Children born prematurely were comparable to an age- and sex-matched control group with regards to almost all cardiopulmonary exercise variables. • A significantly higher OUES, a surrogate parameter for VO 2 peak was found for the group of former preterm children, most likely reflecting on more physical exercise in this group. Importantly, there were no signs of impaired cardiopulmonary function in the group of former preterm children.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Cardiopulmonary exercise testing; Habitual exercise; Premature birth; Sports

Jumping into a Healthier Future: Trampolining for Increasing Physical Activity in Children - Schöffl, Volker Rainer; Schöffl, Isabelle; Ehrlich, Benedikt; Rottermann, Kathrin; Weigelt, Annika; Dittrich, Sven; Schoeffl, Volker (Sports Medicine - Open, 2021)
Objectives: Physical activity in children and adolescents has positive effects on cardiopulmonary function in this age group as well as later in life. As poor cardiopulmonary function is associated with higher mortality and morbidity, increasing physical activity especially in children needs to become a priority. Trampoline jumping is widely appreciated in children. The objective was to investigate its use as a possible training modality. Methods: Fifteen healthy children (10 boys and 5 girls) with a mean age of 8.8 years undertook one outdoor incremental running test using a mobile cardiopulmonary exercise testing unit. After a rest period of at least 2 weeks, a trampoline test using the mobile unit was realized by all participants consisting of a 5-min interval of moderate-intensity jumping and two high-intensity intervals with vigorous jumping for 2 min, interspersed with 1-min rests. Results: During the interval of moderate intensity, the children achieved V̇ O2-values slightly higher than the first ventilatory threshold (VT1) and during the high-intensity interval comparable to the second ventilatory threshold (VT2) of the outdoor incremental running test. They were able to maintain these values for the duration of the respective intervals. The maximum values recorded during the trampoline test were significantly higher than during the outdoor incremental running test. Conclusion: Trampoline jumping is an adequate tool for implementing high-intensity interval training as well as moderate-intensity continuous training in children. As it is a readily available training device and is greatly enjoyed in this age group, it could be implemented in exercise interventions.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Cardiopulmonary function; Children; Exercise testing; Pediatric cardiology; Pediatrics; Physical activity; Rehabilitation; Training; Training modalities

Mountains and Waves: Fontan Circulation in Different Environmental Conditions - Peter, S.; Müller, N.; Schöffl, Isabelle; Michaelis, A.; Weickmann, J.; Klehs, S.; Härtel, J.; Kratz, T.; Dähnert, I.; Paech, C. (Pediatric Cardiology, 2024)
As surgical options and medical care for patients with univentricular heart physiology continue to improve, leading to increased life expectancy and quality of life, a new population of Fontan patients is growing up with the desire to participate in leisure activities, including aquatic activities, high-altitude stays, and air travel. Due to significant data gaps and insufficient experience, current guidelines do not provide clear recommendations, leading to uncertainty and sometimes restrictive patient management. This review summarizes new insights and the current state of research on this subject and provides an overview of the long overdue change in policies toward less restrictive counseling for Fontan patients regarding swimming, diving, high-altitude stays, and air travel. The current review summarizes the physiologic impact of aquatic and high-altitude activities on the cardiovascular system and presents currently available data on this topic in Fontan patients. Patients with Fontan circulation in good clinical shape can tolerate activities in the water and in the mountains as well as air traveling without critical events. In order to be able to make general recommendations, further studies with larger numbers of cases must be carried out.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Altitude; Diving; Fontan; Hypobaric medicine; Hypoxia; Swimming

Myocarditis and sports in the young: data from a nationwide registry on myocarditis—“MYKKE-Sport” - Schöffl, Isabelle; Holler, Sophia; Dittrich, Sven; Pickardt, Thomas; Opgen-Rhein, Bernd; Boehne, Martin; Wannenmacher, Bardo; Reineke, Katja; Wiegand, Gesa; Hecht, Tobias; Kaestner, Michael; Messroghli, Daniel; et al. (Frontiers in Sports and Active Living, 2023)
Background: Myocarditis represents one of the most common causes of Sudden Cardiac Death in children. Myocardial involvement during a viral infection is believed to be higher as a consequence of intensive exertion. Recommendations for return to sports are based on cohort and case studies only. This study aims to investigate the relationship between physical activity and myocarditis in the young. Patient: Every patient in the MYKKE registry fulfilling criteria for suspicion of myocarditis was sent a questionnaire regarding the physical activity before, during and after the onset of myocarditis. Method: This study is a subproject within the MYKKE registry, a multicenter registry for children and adolescents with suspected myocarditis. The observation period for this analysis was 93 months (September 2013–June 2021). Anamnestic, cardiac magnetic resonance images, echocardiography, biopsy and laboratory records from every patient were retrieved from the MYKKE registry database. Results: 58 patients (mean age 14.6 years) were enrolled from 10 centers. Most patients participated in curricular physical activity and 36% in competitive sports before the onset of myocarditis. There was no significant difference of heart function at admission between the physically active and inactive subjects (ejection fraction of 51.8 ± 8.6% for the active group vs. 54.4 ± 7.7% for the inactive group). The recommendations regarding the return to sports varied widely and followed current guidelines in 45%. Most patients did not receive an exercise test before returning to sports. Conclusion: Sports before the onset of myocarditis was not associated with a more severe outcome. There is still a discrepancy between current literature and actual recommendations given by health care providers. The fact that most participants did not receive an exercise test before being cleared for sports represents a serious omission.
CRIS-Team Scopus Importer:2023-07-21
Keywords: cardiomyopathy; heart muscle infection; prevention; return to sports; sudden cardiac death

New kids on the CPET: age-appropriate outdoor cardiopulmonary exercise testing in preschoolers - Rottermann, Kathrin; Weigelt, Annika; Staebler, Tim; Ehrlich, Benedikt; Dittrich, Sven; Schöffl, Isabelle (European Journal of Applied Physiology, 2022)
Purpose: Cardiopulmonary exercise testing (CPET) in preschoolers (4–6 years) represents a challenge. Most studies investigating CPET have been limited to older children (> 8 year). However, knowledge of the performance of small children is essential for evaluating their cardiorespiratory fitness. This study strives to compare a modified Bruce protocol with a new age-appropriate incremental CPET during natural movement running outdoors, using a mobile device. Methods: A group of 22 4–6-year-old healthy children was tested indoor on a treadmill (TM) using the modified Bruce protocol. The results were compared with a self-paced incremental running test, using a mobile CPET device in an outdoor park. The speeds were described as (1) slow walking, (2) slow running, (3) regular running, and (4) running with full speed as long as possible. Results: Mean exercise time outdoors (6,57 min) was significantly shorter than on the treadmill (11,20 min), V˙ O2peak (51.1 ml/min/kg vs. 40.1 ml/min/kg), RER (1.1 vs. 0.98) and important CPET parameters such as V˙ Emax, O2pulse, heart rate and breath rate were significantly higher outdoors. The submaximal parameter OUES was comparable between both the tests. Conclusions: Testing very young children with a mobile device is a new alternative to treadmill testing. With a significantly shorter test duration, significantly higher values for almost all cardiopulmonary variables can be achieved without losing the ability to determine VT1 and VT2. It avoids common treadmill problems and allows for individualized exercise testing. The aim is to standardize exercise times with individual protocols instead of standardizing protocols with individual exercise times, allowing for better comparability.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Age-appropriate; Cardiopulmonary exercise test; CPET; Outdoor; Pediatric; Preschooler

Open Field Exercise Testing in Pediatric Congenital Heart Disease Patients: A Subsumption of Cardiovascular Parameters - Rückert, J.; Michaelis, A.; Markel, F.; Kalden, P.; Löffelbein, F.; Klehs, S.; Dähnert, I.; Schöffl, Isabelle; Rottermann, Kathrin; Paech, C. (Pediatric Cardiology, 2023)
Heart failure is a common phenomenon in congenital heart disease patients. Cardiopulmonary exercise testing is used for a reliable assessment of heart failure but is still challenging, especially for young children. Implementing mobile cardiopulmonary exercise testing (CPET) can close that diagnostic gap. While average values for healthy children have already been published, this study aims to describe typical ranges of cardiovascular performance parameters of young children with congenital heart disease performing an 8-min running cardiopulmonary exercise test. Children aged 4–8 years with common congenital heart defects after corrective surgery (Tetralogy of Fallot; transposition of the great arteries and univentricular hearts after palliation) were included. The outdoor running protocol consisted of slow walking, slow jogging, fast jogging, and maximum speed running. Each exercise was performed for 2 min, except the last, in which children were instructed to keep up maximal speed as long as possible. A total of 78 children (45 male/33 female, mean age 6,24) with congenital heart disease participated in the study, of which 97% completed the CPET successfully. A detailed description of participating patients, including data on cardiac function and subjective fitness levels, is given to help physicians use this method to classify their patients. This study presents a typical range for cardiovascular performance parameters in a population of 4–8-year-old children with congenital heart disease tested in a newly developed outdoor running protocol for CPET.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Children; Congenital heart disease; CPET; Exercise testing

Open field stress testing: finally an optimal method in young children? Reference values for mobile cardiopulmonary exercise testing in healthy children aged 4-8 years - Kalden, Philipp; Schöffl, Isabelle; Rottermann, Kathrin; Loeffelbein, Florian; Michaelis, Anna; Markel, Franziska; Brosig, Susann; Gebauer, Roman Antonin; Daehnert, Ingo; Paech, Christian (Cardiology in the Young, 2021)
Introduction: Cardiopulmonary exercise testing represents the diagnostic tool for determining cardiopulmonary function. Especially in small children, exercise testing is extremely challenging. To address this problem, field testing has been implemented using small mobile devices. This study aims at using this protocol for developing normal values for cardiopulmonary exercise testing in very young children. Material and methods: Healthy children aged 4-8 years were recruited. All children were tested according to an outdoor protocol, in which they were instructed to walk, then run slowly, then a little harder and at last run at full speed. Each step lasted for 2 minutes, except the last step, in which the children were instructed to maintain as long as possible. Results: A total of 104 children (64 female/35 male, mean age 6.6 years) performed outdoor cardiopulmonary exercise testing using a mobile device. Almost all tests were completed successfully (95%). Despite a predominance of female study subjects, anthropometric values did not differ between boys and girls. V?O (2) peak/kg, respiratory exchange ratio, VT1, heart rate at VT1, and time of exercise were also comparable between sexes. Generally, a tendency of higher maximal oxygen uptake could be observed in older children. Conclusion: Open field mobile cardiopulmonary exercise testing represents a novel approach in very young children. In this study, we were able to determine normal values of maximal oxygen uptake and OUES/kg for 4-8-year-old children. The method is easy to achieve and safe.
CRIS-Team WoS Importer:2021-12-17

Outdoor Uphill Exercise Testing for Trail Runners, a More Suitable Method? - Schöffl, Isabelle; Jasinski, Dominik; Ehrlich, Benedikt; Dittrich, Sven; Schoeffl, Volker (Journal of Human Kinetics, 2021)
There is extensive knowledge about uphill running on a treadmill, although paucity regarding the influence of uphill trail running on exercise capacity in runners. The purpose of this study was to compare an uphill field test with a treadmill test with 1% inclination especially considering cardiopulmonary exercise variables. The difference in those tests between a group of trail runners and a group of road runners was tested for establishing a test specifically for trail runners. Ten male endurance road runners and ten male trail runners performed one maximal incremental treadmill test with 1% inclination and a maximal incremental field test on a hill at 16% inclination which they were instructed to run up four times for three minutes, each time with a higher pace. A mobile cardiopulmonary exercise testing unit was used to measure ventilation. There were no significant differences between trail runners and road runners. The equivalence factor was comparable between both groups. VO2peak was comparable for both test protocols. However, there was a significant difference between the two test protocols regarding lactate concentration, the respiratory exchange ratio, running cost, heart rate, Breathing reserve, and O-2pulse. The greater lactate concentration and running cost recorded uphill indicate a higher energy demand during trail running than level road running.
CRIS-Team WoS Importer:2021-08-13

Pediatric Aspects in Young Rock Climbers - Schöffl, Isabelle; Schöffl, Volker (Springer International Publishing, 2022)
As climbing consists of power and endurance aspects, it represents an ideal activity for children and adolescents. In addition to promoting the entire muscular system, it advances cognitive and mental function. However, the climbers need to be introduced to climbing stepwise according to their capabilities. Their development and individual responsibility need to be reevaluated at regular intervals. High-intensive training modalities used in elite sports should be avoided, as they can increase the risk of early arthrosis in the small finger joints as well as epiphyseal fractures. Finger pain during and after exercise must be recognized as an early warning sign.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Child development; Children; Epiphyseal fracture; Growth

Primary Periphyseal Stress Injuries of the Fingers in Adolescent Climbers: A Critical Review - Jones, Gareth; Johnson, Rowena; Schöffl, Volker Rainer; Schöffl, Isabelle; Lutter, Chris; Johnson, Mark; Halsey, Tim (Current Sports Medicine Reports, 2022)
The worldwide rise in popularity of climbing and development of climbing as a competitive sport is reflected by its debut at the 2021 Summer Olympic Games in Tokyo. Digital primary periphyseal stress injuries in adolescent climbers may pose a significant risk to long-term skeletal health. The aim of this article is to critically review research on the diagnosis and management of primary periphyseal stress injuries of the fingers in adolescent climbers. We adopted a systematic approach to searching for relevant literature. Articles were identified after searches of the following electronic databases: Discover, Academic Search Complete, PubMed, Embase, SPORTDiscus, and ScienceDirect. Conclusive evidence suggests digital primary periphyseal stress injuries are a consequence of repetitive microtrauma. Pain reported by adolescent climbers on the dorsal aspect of the proximal interphalangeal joint should be investigated promptly to avoid serious negative consequences. Clinicians should be aware of the efficacy of imaging techniques to inform a clinical diagnosis. A conservative management approach is preferred but in rare cases surgical intervention may be necessary. A diagnostic and therapeutic algorithm for digital primary periphyseal stress injuries is presented.
CRIS-Team WoS Importer:2023-01-13

Sports despite masks: no negative effects of FFP2 face masks on cardiopulmonary exercise capacity in children - Weigelt, Annika; Schöffl, Isabelle; Rottermann, Kathrin; Wällisch, Wolfgang; Müller, Susanna; Dittrich, Sven; Hübner, Matthias (European Journal of Pediatrics, 2023)
Face masks were recognized as one of the most effective ways to prevent the spread of the COVID-19 virus in adults. These benefits were extended to children and adolescents. However, the fear of negative consequences from wearing a face mask during physical exercise led to cancellations of physical education lessons. This further decreased the amount of physical activity available to children and adolescents during the pandemic. However, there is little published data on the potential adverse effects of wearing the most effective and partially mandatory FFP2/N95 face masks during PE or physical activity (PA) in this age. Even though the pandemic has been declared as passed by the WHO, the rise of a new pandemic and thus the use of face masks for limiting its spread is inevitable, so we need to be better prepared for alternative options to lockdown and limitation of PA in such a scenario. Twenty healthy children aged 8–10 years performed two identical cardiopulmonary exercise tests as an incremental step test on a treadmill within an interval of 2 weeks, one time without wearing a protective mask and one time wearing an FFP2 mask. The cardiopulmonary exercise parameter and especially the end-expiratory gas exchange for oxygen and carbon dioxide (petO2 and petCO2) were documented for each step, at rest and 1 min after reaching physical exhaustion. Twelve boys (mean age 8.5 ± 1.4 years) and 8 girls (mean age 8.8 ± 1.4 years) showed no adverse events until maximal exertion. The mean parameters measured at peak exercise did not differ significantly between both examinations (mean peak VO2 = 42.7 ± 9.5 vs 47.8 ± 12.9 ml/min/kg, p = 0.097, mean O2pulse 7.84 ± 1.9 ml/min vs. 6.89 ± 1.8, p = 0.064, mean VE/VCO2slope 33.4 ± 5.9 vs. 34.0 ± 5.3, p = 0.689). The only significant difference was the respiratory exchange rate (RER, 1.01 ± 0.08 vs 0.95 ± 0.08, p = 0.004). The measured respiratory gases (end-tidal O2 and CO2) decreased and respectively increased significantly in almost every step when wearing an FFP2 mask. However, these levels were well below hypercapnia and above hypoxia. Conclusion: In this study, no significant differences in the cardiorespiratory function at peak exercise could be discerned when wearing an FFP2/N95 face mask. While the end-tidal values for CO2 increased significantly and the end-tidal values for O2 decreased significantly, these values did never reach levels of hypercapnia or hypoxia. Furthermore, the children terminated the exercise at a lower RER and heart rate (HR) suggesting a subconscious awareness of the higher strain. Since the detrimental effects of limiting sports during the pandemic are well documented, stopping PE lessons altogether because of the minor physiological effects of wearing these masks instead of simply stopping pushing children to perform at their best seems premature and should be reconsidered in the future. What is Known: • Wearing a face mask has an influence on psychological, social, and physiological functions in adults. • Because of the observed effects of wearing face masks in adults, physical activity in children was limited during the pandemic. What is New: • Wearing an FFP2/N95 mask during physical activity did not lead to hypercapnia or hypoxia in children in this study. • Even though end-tidal CO2 values were significantly higher and end-tidal O2 values significantly lower when wearing an FFP2/N95 face mask, no pathological values were reached.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Coronavirus; COVID-19; End-tidal CO; End-tidal O; Oxygen saturation; Treadmill testing; VO

Sports-Medical Supervision of Competition Climbers and Climbing Competitions - Schöffl, Volker; Schöffl, Isabelle (Springer International Publishing, 2022)
Conducting yearly team examinations and serving as a medical officer at climbing competitions are central elements in taking care of competitive climbers. The team examination plays an important role in early injury detection and is an opportunity to establish a trusting relationship so that the athletes approach the team physician openly with questions or concerns. It is based on the recommendations of the national Olympic Committees and the Medical Commission of the IFSC, which recommend performing a sports-medical and an orthopedic exam, a resting ECG, a spiroergometry with stress ECG, a cardiac echography, a laboratory analysis, and body fat measurement. In climbers, we also always perform an ultrasound examination of the hand and fingers. During climbing competitions, the most frequent treatments are the care of acute traumata need and many superficial skin bleeds. Nevertheless, the occasional internal medical condition also occurs. A central part in being an effective medical supervisor in competitions is organization and coordination of the whole medical team and the communication with athletes, judges, and other officials—it is always teamwork. To achieve this, specific insight into climbing medicine is essential.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Anti-doping; Cardiac echography; Competition; Spiroergometry; Team examination

The Fontan and the Sea: First-in-Man Data on Swimming and Diving Physiology in Fontan Patients - Paech, C.; Gebauer, R. A.; Weidenbach, M.; Mensch, S.; Kalden, P.; Markel, F.; Michaelis, A.; Schöffl, Isabelle; Daehnert, I.; Riede, F. T.; Rudrich, P.; Wolfarth, B.; et al. (Pediatric Cardiology, 2021)
While swimming represents a popular recreational activity, the immersion of the human body into the water requires a complex physiologic adaption of the whole cardiopulmonary and circulatory system. While this sport is regarded as beneficial, especially in cardiovascular patients, current guidelines hypothesized a possible hazardous effect of swimming and especially diving in patients with univentricular hearts after Fontan palliation. Yet, actual data to underline or contradict these assumptions are lacking. Therefore, this study aimed to conduct a first feasibility study for the evaluation of these effects on Fontan physiology and elucidate the gap of evidence currently preventing patients after Fontan palliation from being restricted from swimming or diving on doctoral advice. Patients recruited from the Heart Center Leipzig, Department of pediatric cardiology, underwent spiroergometry treadmill testing followed by a spiroergometry swimming stress test in a counter current pool. Physiologic data were recorded. A short apnea diving test was performed. The current study found similar physiologic reactions comparing treadmill and swimming exercise stress testing. Heart rate response and oxygen uptake were comparable on land and in the water. This study presents the first-in-man data on swimming and diving in Fontan patients. In this small study cohort of three Fontan patients, there were no adverse events triggered by swimming and breath-hold diving seen. Basically, the physiologic response to exercise was comparable on land and in the water.
CRIS-Team WoS Importer:2021-06-11

What to Examine in Youth Climbing Athletes: Yearly Examination of the German Climbing Team and its Consequences - Schöffl, Isabelle; Lutter, Christoph; Schöffl, Volker (Sportverletzung-Sportschaden, 2019)
Objective This article presents the results of the yearly medical examination performed on all our national climbing athletes in 2016 and 2017. Methods Our yearly athlete examination follows the Olympic guidelines and those of the Medical Commission of the International Federation of Sport Climbing. It consists of echocardiography, spiroergometry, a general blood examination, body fat measurement as well as a paediatric and orthopaedic clinical examination. In addition, a yearly ultrasound examination is performed on the fingers to detect pathologies and measure the width of the growth plates. The years 2016/2017 were evaluated. Results Team examinations were undertaken in 17 girls and 23 boys. The mean age was 17.5 years (18.3 years for the boys and 17.4 years for the girls). They had been climbing for 10.9 years on average (the boys for 11.3 and the girls for 10.3 years). Typical findings were susceptibility to infection, musculoskeletal injuries and, in one case, severe headaches. 36% of our athletes had to take a break from climbing due to injury or illness. Most of these breaks were due to infections (7 in total), most of them minor inspiratory or gastrointestinal. One athlete suffered from severe pneumonia during a World Cup in Japan. The other pauses were due to finger injuries (2), foot injuries (2), and injuries to the shoulder and biceps (2). Conclusion The yearly team examination plays an important role in early injury detection. It helps to establish a relationship based on trust, encouraging athletes to approach the team physician openly with questions or concerns.
CRIS-Team Scopus Importer:2019-12-20
Keywords: finger injuries; national team; rock climbing; sport climbing; sports medical exam; team exam